Corrosion Inhibition of Titanium in Acidic Media Containing Fluoride with Bixin. Issue 4 (2009) - Chauhan, Jinendra Singh; Gupta, D. K.
Abstract : The bixin in acidic media were tested for corrosion inhibition of Ti in 0.5 N sulphuric acid and 0.1 N HCl solution at 30 to 40 °C temperature range by electrochemical methods. It reveals that bixin works as a corrosion inhibitor in halide media and protect the metals from the corrosion with great efficiency